A super-hydrophobic corrosion-resistant coating for stainless steel and a method for preparing the same

By forming a superhydrophobic and corrosion-resistant coating of Schiff base polyester and nano-silica on the surface of stainless steel, the problems of insufficient adhesion between stainless steel and acrylic resin coating and high toxicity of fluorine compounds are solved, achieving high adhesion and excellent hydrophobic and corrosion-resistant properties.

CN120623854BActive Publication Date: 2025-11-21XINTIAN HEXIN STAINLESS STEEL PROD CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510924046.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-04
Publication Date
2025-11-21
Estimated Expiration
2045-07-04

AI Technical Summary

Technical Problem

The adhesion between stainless steel and acrylic resin coating is low, which makes the coating prone to peeling and bubbling, affecting its anti-corrosion performance. At the same time, existing superhydrophobic coatings contain highly toxic fluorinated compounds, posing ecological problems.

Method used

Schiff base polyester is generated by polymerizing tris(2-aminoethyl)amine condensed p-formylbenzoic acid Schiff base and diol compound. It is then compounded with nano-silica and added to acrylic resin. Through thermosetting, a superhydrophobic and corrosion-resistant coating is formed. The coating contains hyperbranched molecular chains and long alkyl chains that form strong coordination with the stainless steel surface.

Benefits of technology

It significantly improves the hydrophobicity and salt spray resistance of the coating, while enhancing the adhesion between the coating and the stainless steel surface, achieving a green and environmentally friendly superhydrophobic effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0005484061140000021
    Figure BDA0005484061140000021
  • Figure BDA0005484061140000022
    Figure BDA0005484061140000022
Patent Text Reader

Abstract

The present application relates to the technical fields of super-hydrophobic coating, and discloses a super-hydrophobic corrosion-resistant coating for stainless steel and a preparation method thereof, wherein a Schiff base polyester is obtained by reacting tris(2-aminoethyl)amine p-formylbenzoic acid and a dihydric compound, and then the Schiff base polyester is sprayed on the surface of stainless steel together with acrylic resin, nano-silicon dioxide and the like, and heat-cured to obtain the super-hydrophobic corrosion-resistant coating.The long alkyl chain, ester group and benzene ring structure of the Schiff base polyester form a hydrophobic network in the acrylic resin coating, and in combination with the micro-nano rough structure formed by the nano-silicon dioxide in the coating, the coating is endowed with excellent super-hydrophobic and salt-fog-resistant corrosion-resistant properties.The Schiff base polyester contains a large number of nitrogen-containing Schiff base groups, which form a strong coordination with iron atoms on the surface of the stainless steel, thereby improving the adhesion of the coating to the surface of the stainless steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of superhydrophobic coating technology, specifically to a superhydrophobic corrosion-resistant coating for stainless steel and its preparation method. Background Technology

[0002] Although stainless steel has strong corrosion resistance, it is still prone to corrosion and rusting in harsh environments such as chemical plants and marine climates, thus requiring the application of anti-corrosion coatings. Superhydrophobic coatings have excellent water resistance, corrosion resistance, and self-cleaning properties, and are widely used. They typically involve adding nanofillers to the coating to form a micro-nano rough structure on the surface, while simultaneously introducing hydrophobic structures such as fluorine and silicon into the coating to impart superhydrophobic properties. However, fluorine compounds are highly toxic and pose serious ecological problems.

[0003] Acrylic resin coatings are widely used in woodworking, automotive, shipbuilding, and construction due to their high transparency, good toughness, and ease of application. However, the smooth surface of stainless steel results in low adhesion between the resin and the coating, leading to peeling and blistering, which affects its corrosion resistance. Patent application CN117683188A discloses a fluorosiloxane-polyester-acrylate elastomer resin and its preparation method, coating components, and applications. The prepared coating exhibits excellent hydrophobicity and mechanical toughness, and shows good adhesion to stainless steel and aluminum alloys. However, this coating requires the addition of fluorine-containing compounds, and it does not demonstrate good salt spray corrosion resistance. Summary of the Invention

[0004] This invention solves the problem of low adhesion between acrylic resin and substrates such as stainless steel, while also endowing stainless steel with unique superhydrophobic properties.

[0005] The technical solution of this invention is: a method for preparing a superhydrophobic and corrosion-resistant coating.

[0006] The technical solution of this invention is: a method for preparing a superhydrophobic and corrosion-resistant coating.

[0007] (1) Add 4-formylbenzoic acid and sodium hydroxide to ethanol, stir, and then add tris(2-aminoethyl)amine. Control the molar ratio of 4-formylbenzoic acid, sodium hydroxide, and tris(2-aminoethyl)amine to (3-3.6):(3-3.6):1. Heat to 40-55℃ and react for 2-3 hours. Add 10-37% hydrochloric acid solution dropwise to adjust the pH to 5-6. After filtration, wash with ethanol. Recrystallize the product in dichloromethane to obtain the Schiff base of tris(2-aminoethyl)amine condensed with p-formylbenzoic acid. The preparation reaction formula is as follows:

[0008]

[0009] (2) Add xylene solvent, tris(2-aminoethyl)amine p-formylbenzoic acid Schiff base, diol compound, and p-toluenesulfonic acid TsOH to a flask. React under a nitrogen atmosphere, cool in an ice-water bath, filter, wash with ethanol and dichloromethane, and dry to obtain the Schiff base polyester. The preparation reaction formula is:

[0010]

[0011] (3) Add xylene solvent, acrylic resin, Schiff base polyester, nano silica and defoamer to the container, stir and spray on the stainless steel surface, and perform heat curing to obtain a superhydrophobic and corrosion resistant coating.

[0012] Furthermore, in (2), the molar ratio of tris(2-aminoethyl)amine condensed p-formylbenzoic acid Schiff base, diol compound, and p-toluenesulfonic acid is 1:(1.4-1.6):(0.03-0.04).

[0013] Furthermore, the structural formula of the diol compound is as follows: n is between 12 and 18.

[0014] Furthermore, in (2), the reaction temperature is 130-140℃ and the reaction time is 24-36h.

[0015] Furthermore, in (3), the mass ratio of acrylic resin, Schiff base polyester, nano silica and defoamer is 100:(20-50):(3-10):(0.5-0.8).

[0016] Furthermore, (3) the heat curing process involves baking at 100-120℃ for 4-6 hours.

[0017] Furthermore, superhydrophobic and corrosion-resistant coatings are applied to stainless steel.

[0018] The beneficial technical effects of this invention are as follows: a Schiff base of tri(2-aminoethyl)amine condensed p-formylbenzoic acid and diol compounds such as 3-(hexadecyloxy)prop-1,2-diol are polymerized to obtain a Schiff base polyester, which is then compounded with nano-silica and added to acrylic resin and cured to obtain a superhydrophobic and corrosion-resistant coating for stainless steel.

[0019] The Schiff base polyester of this invention contains hyperbranched molecular chains and long alkyl chains, which form a physical chain entanglement with the acrylic resin molecular chains. This allows the hydrophobic long alkyl chains, ester groups, and benzene ring structures to be uniformly dispersed in the acrylic resin coating, forming a hydrophobic network. This significantly improves the hydrophobicity of the coating. Combined with the micro-nano rough structure formed by nano-silica in the coating, it endows the coating with excellent superhydrophobicity and salt spray resistance. It does not require the addition of fluorine-containing compounds and is environmentally friendly.

[0020] The Schiff base polyester of the present invention contains a large number of nitrogen-containing Schiff base groups, which form a strong coordination effect with iron atoms on the stainless steel surface, thereby improving the adhesion between the coating and the stainless steel surface. Attached Figure Description Detailed Implementation

[0021] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] Example 1

[0023] (1) Add 150 mmol of 4-formylbenzoic acid and 150 mmol of sodium hydroxide to 700 mL of ethanol, stir, add 50 mmol of tris(2-aminoethyl)amine, heat to 50 °C, react for 3 h, add dropwise 20% hydrochloric acid solution, adjust pH to 5, filter, wash with ethanol, recrystallize the product in dichloromethane to obtain tris(2-aminoethyl)amine condensed p-formylbenzoic acid Schiff base.

[0024] (2) Add 300 mL xylene solvent, 50 mmol tris(2-aminoethyl)amine p-formylbenzoic acid Schiff base, 75 mmol 3-(hexadecyloxy)prop-1,2-diol and 2 mmol p-toluenesulfonic acid to a flask, heat to 140 °C under a nitrogen atmosphere, react for 24 h, cool in an ice-water bath, filter, wash with ethanol and dichloromethane, and dry to obtain Schiff base polyester.

[0025] (3) Add 1.2L xylene solvent, 1kg acrylic resin, 200g Schiff base polyester, 550g nano silica and 5g defoamer STA-6300 to the container, shear and disperse, then spray on the stainless steel surface and bake at 110℃ for 6h to obtain a superhydrophobic and corrosion resistant coating.

[0026] Example 2

[0027] (1) Add 180 mmol of 4-formylbenzoic acid and 180 mmol of sodium hydroxide to 800 mL of ethanol, stir, add 50 mmol of tris(2-aminoethyl)amine, heat to 55 °C, react for 2 h, add dropwise 37% hydrochloric acid solution, adjust pH to 6, filter, wash with ethanol, recrystallize the product in dichloromethane to obtain tris(2-aminoethyl)amine condensed p-formylbenzoic acid Schiff base.

[0028] (2) Add 400 mL xylene solvent, 50 mmol tris(2-aminoethyl)amine p-formylbenzoic acid Schiff base, 70 mmol 3-octadecyloxy-1,2-propanediol, and 1.5 mmol p-toluenesulfonic acid to a flask. Heat to 130 °C under a nitrogen atmosphere and react for 36 h. Cool in an ice-water bath, filter, wash with ethanol and dichloromethane, and dry to obtain Schiff base polyester.

[0029] (3) Add 1.6L xylene solvent, 1kg acrylic resin, 350g Schiff base polyester, 650g nano silica and 8g defoamer STA-6300 to the container, shear and disperse, then spray on the stainless steel surface and bake at 120℃ for 4h to obtain a superhydrophobic and corrosion resistant coating.

[0030] Example 3

[0031] (1) Add 160 mmol of 4-formylbenzoic acid and 160 mmol of sodium hydroxide to 800 mL of ethanol, stir, add 50 mmol of tris(2-aminoethyl)amine, heat to 40 °C, react for 3 h, add dropwise 10% hydrochloric acid solution to adjust pH to 6, filter, wash with ethanol, recrystallize the product in dichloromethane to obtain tris(2-aminoethyl)amine condensed p-formylbenzoic acid Schiff base.

[0032] (2) Add 400 mL xylene solvent, 50 mmol tris(2-aminoethyl)amine p-formylbenzoic acid Schiff base, 80 mmol 3-(dodecyloxy)propane-1,2-diol, and 2 mmol p-toluenesulfonic acid to a flask. Heat to 140 °C under a nitrogen atmosphere and react for 24 h. Cool in an ice-water bath, filter, wash with ethanol and dichloromethane, and dry to obtain Schiff base polyester.

[0033] (3) Add 1.5L xylene solvent, 1kg acrylic resin, 500g Schiff base polyester, 400g nano silica and 6g defoamer STA-6300 to the container, shear and disperse, then spray on the stainless steel surface and bake at 110℃ for 6h to obtain a superhydrophobic and corrosion resistant coating.

[0034] Comparative Example 1

[0035] (1) Add 1.2L xylene solvent, 1kg acrylic resin, 550g nano silica and 5g defoamer STA-6300 to the container, shear and disperse, then spray on the stainless steel surface and bake at 110℃ for 6h to obtain a superhydrophobic and corrosion resistant coating.

[0036] Comparative Example 2

[0037] (1) Add 100 mmol of 4-formylbenzoic acid and 100 mmol of sodium hydroxide to 700 mL of ethanol, stir, then add 50 mmol of 2,2'-diamino-N-methyldiethylamine, heat to 50 °C, react for 3 h, add dropwise 20% hydrochloric acid solution to adjust the pH to 5, filter, wash with ethanol, and recrystallize the product in dichloromethane to obtain the Schiff base of 2,2'-diamino-N-methyldiethylamine condensed p-formylbenzoic acid. The structural formula is...

[0038] (2) Add 300 mL of xylene solvent, 75 mmol of 2,2'-diamino-N-methyldiethylamine p-formylbenzoic acid Schiff base, 75 mmol of 3-(hexadecyloxy)prop-1,2-diol and 2 mmol of p-toluenesulfonic acid to a flask, heat to 140 °C under a nitrogen atmosphere, react for 24 h, cool in an ice-water bath, filter, wash with ethanol and dichloromethane, and dry to obtain Schiff base polyester.

[0039] (3) Add 1.2L xylene solvent, 1kg acrylic resin, 200g Schiff base polyester, 550g nano silica and 5g defoamer STA-6300 to the container, shear and disperse, then spray on the stainless steel surface and bake at 110℃ for 6h to obtain a superhydrophobic and corrosion resistant coating.

[0040] Comparative Example 3

[0041] (1) Add 300 mL xylene solvent, 50 mmol trimesic acid, 75 mmol 3-(hexadecyloxy)prop-1,2-diol and 2 mmol p-toluenesulfonic acid to a flask, heat to 140 °C under a nitrogen atmosphere, react for 24 h, cool in an ice-water bath, filter, wash with ethanol and dichloromethane, and dry to obtain polyester.

[0042] (2) Add 1.2L xylene solvent, 1kg acrylic resin, 200g polyester, 550g nano silica and 5g defoamer STA-6300 to the container, shear and disperse, then spray on the stainless steel surface and bake at 110℃ for 6h to obtain a superhydrophobic and corrosion resistant coating.

[0043] Comparative Example 4

[0044] (1) Add 300 mL of xylene solvent, 50 mmol of tris(2-aminoethyl)amine p-formylbenzoic acid Schiff base, and 75 mmol of 1,2-butanediol (structural formula: 2 mmol of p-toluenesulfonic acid was heated to 140 °C in a nitrogen atmosphere and reacted for 24 h. The mixture was then cooled in an ice-water bath, filtered, washed with ethanol and dichloromethane, and dried to obtain Schiff base polyester.

[0045] (2) Add 1.2L xylene solvent, 1kg acrylic resin, 200g Schiff base polyester, 550g nano silica and 5g defoamer STA-6300 to the container, shear and disperse, then spray on the stainless steel surface and bake at 110℃ for 6h to obtain a superhydrophobic and corrosion resistant coating.

[0046] The water contact angle of the coating surface was tested using a contact angle tester. Five water contact angles were measured for each sample, and the average value was taken.

[0047] Salt spray resistance was tested according to GB / T 1771-2007 standard. Coating adhesion grade was tested according to GB / T9286-2021 standard.

[0048] Table 1 Performance test of the coating

[0049]

[0050] After testing, compared with the acrylic resin coating of Comparative Example 1, the water contact angle of the coatings in Examples 1-3 reached 151.3-155.7°, and the salt spray resistance was excellent, with an adhesion grade of 0-1. This was mainly due to the addition of Schiff base polyester, which contains hyperbranched molecular chains and long alkyl chains. These chains form a physical chain entanglement with the acrylic resin molecular chains, allowing the hydrophobic long alkyl chains, ester groups, and benzene ring structures to be uniformly dispersed in the acrylic resin coating, forming a hydrophobic network. This significantly improves the hydrophobicity of the coating. Combined with the micro-nano rough structure formed by nano-silica in the coating, the coating is endowed with excellent superhydrophobicity and salt spray corrosion resistance. At the same time, the Schiff base polyester contains a large number of nitrogen-containing Schiff base groups, which form a strong coordination effect with the iron atoms on the stainless steel surface, thereby improving the adhesion between the coating and the stainless steel surface.

[0051] Comparative Example 2 involved polymerizing 2'-diamino-N-methyldiethylamine condensed with p-formylbenzoic acid Schiff base and 3-(hexadecyloxy)prop-1,2-diol. The resulting Schiff base polyester had a linear structure and lacked hyperbranched molecular chains. This resulted in low physical chain entanglement with acrylic resin, leading to poor compatibility and dispersibility with acrylic resin. Consequently, it was difficult to uniformly disperse the hydrophobic long alkyl chains, ester groups, and benzene ring structures in the acrylic resin coating to form a hydrophobic network. This resulted in a low water contact angle, poor salt spray resistance, and an adhesion grade of only 1.

[0052] Comparative Example 3 uses pyromellitic acid and 3-(hexadecoxy)prop-1,2-diol for polymerization. The resulting polyester does not contain Schiff base groups and has very low coordination with the stainless steel surface, resulting in an adhesion of only grade 2 between the coating and the stainless steel surface.

[0053] Comparative Example 4 uses tris(2-aminoethyl)amine condensed with p-formylbenzoic acid Schiff base and 1,2-butanediol for polymerization reaction. The resulting polyester does not contain hydrophobic alkyl long chains, the coating has a low water contact angle, and poor salt spray corrosion resistance.

[0054] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing a superhydrophobic and corrosion-resistant coating, characterized in that, The method for preparing the superhydrophobic and corrosion-resistant coating is as follows: (1) Add xylene solvent, tris(2-aminoethyl)amine p-formylbenzoic acid Schiff base, diol compound, and p-toluenesulfonic acid to a flask, and carry out the reaction under a nitrogen atmosphere. Cool in an ice-water bath, filter, wash, and dry to obtain Schiff base polyester. (2) Add xylene solvent, acrylic resin, Schiff base polyester, nano silica and defoamer to the container, shear and disperse, then spray on the stainless steel surface and heat cure to obtain a superhydrophobic and corrosion resistant coating. The structural formula of the diol compound is: n is 12-18; The reaction temperature in (1) is 130-140℃, and the reaction time is 24-36h; The preparation method of the tri(2-aminoethyl)amine p-formylbenzoic acid Schiff base is as follows: 4-formylbenzoic acid and sodium hydroxide are added to ethanol, stirred, and then tri(2-aminoethyl)amine is added. The mixture is heated to 40-55℃ and reacted for 2-3 hours. A 10-37% hydrochloric acid solution is added dropwise to adjust the pH to 5-6. After filtration and washing, the product is recrystallized in dichloromethane to obtain the tri(2-aminoethyl)amine p-formylbenzoic acid Schiff base.

2. The method for preparing the superhydrophobic and corrosion-resistant coating according to claim 1, characterized in that, The molar ratio of tris(2-aminoethyl)amine p-formylbenzoic acid Schiff base, diol compound, and p-toluenesulfonic acid in (1) is 1:(1.4-1.6):(0.03-0.04).

3. The method for preparing the superhydrophobic and corrosion-resistant coating according to claim 1, characterized in that, The mass ratio of acrylic resin, Schiff base polyester, nano silica and defoamer in (2) is 100:(20-50):(40-65):(0.5-0.8).

4. The method for preparing the superhydrophobic and corrosion-resistant coating according to claim 1, characterized in that, In step (2), the thermosetting process involves baking at 100-120℃ for 4-6 hours.

5. The method for preparing the superhydrophobic and corrosion-resistant coating according to claim 1, characterized in that, The molar ratio of 4-formylbenzoic acid, sodium hydroxide, and tris(2-aminoethyl)amine is (3-3.6):(3-3.6):

1.

6. A superhydrophobic and corrosion-resistant coating obtained by the preparation method according to any one of claims 1-5.

7. The application of the superhydrophobic corrosion-resistant coating as described in claim 6 in stainless steel.

Citation Information

Patent Citations

  • Fluorosiloxane-polyester-acrylate elastomer resin, and preparation method, coating component and application thereof

    CN117683188A

  • High-temperature self-crosslinking anti-flaming anti-dripping copolyester based on Schiff base structure and preparation method thereof

    CN105273173A

  • Schiff base modified silane / polyurethane antifouling coating as well as preparation method and application thereof

    CN119529653A